Red cliff - John Woo,&d1946-; Terence Chang; Cahn Khan; Guo Zheng; Sheng Heyu; Tony Chiu Wai Leung 1962-; Takeshi Kaneshiro; Fengyi Zhang; Yong You; Zhen Zhang; Zhongguo dian ying ji tuan gong si (Magnolia Home Entertainment, 2010)
Filmmaker John Woo brings Red Cliff, the epic historical drama based on a legendary 208 A.D. battle that heralded the end of the Han Dynasty, to life in this action-packed U.S. theatrical version. A power-hngry Prime Minister-turned-general Cao Cao seeks permission from the Han Dynasty Emperor to organize a southward-bound mission designed to crush the two troublesome warlords who stand in his way, Liu Bei and Sun Quan. Vastly outnumbered by Cao Cao?s brutal, fast-approaching army, the warlords band together to mount a heroic campaign ? unrivaled in history that changes the face of China forever.